2018
DOI: 10.1080/21642583.2018.1531082
|View full text |Cite
|
Sign up to set email alerts
|

The robust shortest path problem for multimodal transportation considering timetable with interval data

Abstract: In the multimodal transport network, due to various uncertain factors such as weather and traffic conditions, the transport time will become uncertain accordingly, besides, railway transport and water transport are usually limited by timetable. These factors will inevitably affect the path selection. The purpose of this study is to seek an optimal transport scheme that considers both the uncertainty of the multimodal transport network and the timetable limit. In view of the uncertainties of the multimodal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In this study, the adopted method of chromosome coding, the crossover operator and the mutation operator were referred to the literature of Liu et al [17].…”
Section: Coding and Evolution Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the adopted method of chromosome coding, the crossover operator and the mutation operator were referred to the literature of Liu et al [17].…”
Section: Coding and Evolution Operationsmentioning
confidence: 99%
“…Rail and water transportation usually have a fixed departure timetable [16], When the goods arrived at the transfer nodes and completed the loading and unloading, it might not be transported immediately due to the timetable limitation of the next mode of transportation [33]. Liu et al [17] indicated that timetable would affect the choice of transportation routes and modes. So it makes more sense to consider timetable in multimodal transportation.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…As shown in Figure 2, NSGA-II mainly includes the following steps: crowding and evolution operations, fast non-dominant sort, crowding distance calculation, tournament selection and elitism strategy. In this paper, the adopted method of chromosome coding, the crossover operator and the mutation operator were referred to the literature of Liu et al (2018), and the other steps were referred to the literature of Peng et al (2021). In the study filed of elite retention strategy, Peng et al (2021) proposed the combined ( μ + λ ) selection with external archiving method to avoid the loss of excellent individuals in the evolutionary process, where μ represents the size of the parental population Z t and λ means the size of a new offspring population Q t .…”
Section: Data-driven Simheuristic Approachmentioning
confidence: 99%
“…Railway and waterway transportation usually have a fixed timetable of departures (Li et al , 2015), which may result in the detention time of goods due to timetable limitation when the goods arrive at the transshipment nodes and complete reloading (Yan et al , 2016). Liu et al (2018) further indicated that timetable would have an impact on the selection of transportation routes and modes.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the solutions provided excellent results when compared to the solutions of classic methods. Liu et al [2018] studied an optimal transport scheme that considered both the uncertainty of the multimodal transport network and the timetable limit. Due to the uncertainties of the multimodal transport network, interval data were used to represent the uncertainty of network weights; hence, RO was utilized.…”
Section: Literature Reviewmentioning
confidence: 99%